Teaching Strategies Used to Deal with Dyslexic Students’ Learning Difficulties - Dewi, Ni Made Indah Purnama (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
Dyslexia is a hereditary, neurodevelopmental learning disorder found to appear in around 10% of the population, characterized by difficulty in reading. Therefore, it needs to be addressed properly by implementing appropriate teaching strategies that can help dyslexic students to learn in the inclusive education setting. However, there is still limited study that provides literature related to the matter. Therefore, this study was a conceptual research aimed to analysing teaching strategies used to deal with the learning difficulties encountered by dyslexic students and provide descriptions related to the dyslexic students’ characteristics along with their learning difficulties. This study is a kind of literature review through library research.The result found that there are four teaching strategies that teachers can use to deal with dyslexic students’ learning difficulties, which are task analysis, explicit phonics instruction, multisensory instruction, and field-dependent approaches. The strategies are adjusted to the characteristics and learning difficulties faced by dyslexic students that include low phonological awareness, slow working memory, rapid naming difficulty, slow processing speed, and low skills automatic development. The strategies emphasise on providing clear, direct instruction with multiple aids and assistance from the teachers. The use of several accommodations are also needed in order to help the dyslexic students to develop their reading skill and deal with their learning difficulties.